PENGARUH EKSTRAK JANTUNG PISANG TERHADAP SIFAT MIKROBIOLOGIS DAN KIMIA NIRA GEWANG SERTA FISIK DAN ORGANOLEPTIK GULA CAIR - Lalel, Herianus Justhianus D; Rubak, Yuliana Tandi; Nalle, Ryan P. L.; Belalawe, Maria U. P. (Jurnal Teknologi Pangan, 2025)
The sap of gebang (Corypha utan Lamk) is  one of the basic materials for making red sugar in Timor Island.  Microbial contaminant reduces the quality of the sap, therefore it should be prevented by using  a  safe natural material as food additives including banana blossom .  This research  has been conducted by using  a simple Completed Random Design (CRD)  with 4 treatments: control (J0), 3% banana blossom extract (J1), 4% banana blossom extract (J2), 5% banana blossom extract (J4) with 4 replications. Parameters observed including total microbes, and pH, of  sap; water activity and organoleptic of liquid sugar. The results show that  adding of banana blossom extract  affects chemical and microbiological properties of the sap as well as physical and organoleptic of the liquid sugar. J0 (5% banana blossom extract) is the best tratment in term of chemical and microbiological properties of the sap as well as physical and organoleptic of the liquid sugar.